Generative design: visualize, program, and create with processing - Bohnacker, Hartmut; GroB, Benedikt; Laub, Julia
Project Selections is a collection of 35 works of generative design created by artists and designers from around the world. In addition to the brilliant images of code driven generative design, there are references in the descriptions of each project to examples of code in subsequent sections of the book that allow you to explore the creation of similar effects. The images are beautifully printed on glossy paper giving the examples a gallery-like feel.